Evaluation of Xenograft Efficacy in Immediate Prosthesis-based Breast Reconstruction. Issue 9 (28th September 2022) - Sobti, Nikhil; Vishwanath, Neel; King, Victor A.; Rao, Vinay; Rhee, Ben; Spake, Carole S.L.; Borrelli, Mimi R.; Akiki, Ronald A.; Breuing, Karl H.
Abstract : Background: The advent of acellular dermal matrix (ADM) has revolutionized prosthesis-based breast reconstruction. However, paucity of human cadaveric tissue has resulted in limitation of supply and increased associated costs, prompting concerted effort to identify xenograft alternatives. Although studies have examined the safety of Artia, a porcine-derived ADM, few have evaluated its clinical efficacy as soft tissue reinforcement. This study uniquely evaluates the clinical efficacy of Artia in implant-based breast reconstruction. Methods: IRB-approved retrospective chart review was conducted to identify 243 consecutive TE-based procedures performed at a tertiary academic medical center between March 2017 and March 2021. Propensity matching was conducted to minimize differences between cohorts. Efficacy metrics, defined as initial tissue expander (TE) fill volume, number of TE fills, and time interval between exchange of TE for final implant, were compared between xenograft (Artia) and allograft (AlloDerm) groups. Results: Patients who underwent Artia-based breast reconstruction achieved superior initial TE fill volume relative to those who underwent AlloDerm-based breast reconstruction via univariate analysis (317.3 ± 185.8 mL versus 286.1 ± 140.4 mL, P < 0.01) when patient and operative characteristics were well-matched. However, linear regression analysis failed to demonstrate difference in efficacy metrics, such as initial TE fill volume ( P = 0.31), ratio between initial TE fill volume and final implant size ( P = 0.19), and number of TE fills ( P = 0.76). Complication rates were comparable between groups. Conclusion: This study suggests that Artia can be used as a safe and efficacious alternative to human-derived ADM in immediate TE-based breast reconstruction.